(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يحاول هذا البحث تسليط الضوء على الوضع الراهن لاستخدام المخبر المدرسي في تدريس العلوم من وجهة نظر مدرسي العلوم في المدارس الثانوية الحكومية والموجهين الاختصاصيين بمحافظة حماه, وقد اعتمد البحث المنهج الوصفي التحليلي, واتخذ الباحث من (الاستبانة) أداةً رئيسة لأخذ آراء أفراد عيّنة الدراسة المؤلفة من (32) مدرساً و(26) موجهاً اختصاصياً. وكانت أهم النتائج التي توصل إليها البحث: ـ تدني نسبة المستخدمین للمخبر المدرسي من المدرسين عندما تتاح لھم إمكانیة استخدامها حیث بلغت نسبتهم (40,63)%. وكانت أهم المعوقات التي تحول دون استخدام المخبر من وجهة نظر مدرسي العلوم والموجهين الاختصاصيين كثرة أعداد الطلاب, ونقص التجهيزات, وعدم تواجد محضر المخبر المتخصص. أما ما يتصل بالفروق بين تقديرات المدرسين و الموجهين الاختصاصيين لأهم معوقات استخدام المخبر في التدريس, فقد دلت النتائج على عدم وجود فروق ذات دلالة إحصائية تشير إلى ذلك, وهذا يعني أن آراء المدرسين حول هذه المعوقات لا تختلف عن آراء الموجهين الاختصاصيين. This research tries to highlight the current situation of the use of school laboratories in science education from the viewpoint of science teachers in public secondary schools and specialist instructors in the governorate of Hama. The research adopts the descriptive analytical method, and the researcher uses the questionnaire a main tool to collect the views of sample of the study, which consists of (32) teacher and (26) specialists. The main findings of the research are: the low percentage of users of the school laboratory by teachers even when given the opportunity to the same. The main obstacles that prevent the use of laboratories from the viewpoint of science teachers and mentors are the large numbers of students, and lack of equipment, and the absence of the lab supervisors themselves. The relation to the differences between the estimates of specialists, teachers and mentors of the main obstacles to the use of laboratory teaching, the results indicated that there were no statistically significant differences to indicate that, this means that the views of teachers about these constraints do not differ from the views of specialists.